ENGAGING NON-ENGLISH DEPARTMENT STUDENTS TO SPEAK: A CHALLENGING PATH - Fitria Muji Pratawati (Journal of English for Academic and Specific Purposes (JEASP), 2019)
This study aimed at sharing how the teacher initiates their students to speak. All efforts have been done in class in order to keep the class alive and students were active in joining the lesson. The students were from non-English department who studied ESP. They were from different major but still in one generation of the State Universities in Malang, East Java-Indonesia. This created the point of view that some students tend to take this course only as the requirement to fulfill their credits in two semesters. Therefore, the role of English teacher dealing with boosting students’ speaking awareness is very pivotal. The result were students tended to be more actively engaged in the class joining the activities given to them, such as debate and making video related their major. Then, this study suggests the teaching practitioners always considering the good atmosphere given to the students before the lesson begins. So, this will be the initial part of making them comfort in class and try to have teamwork with them to succeed the objective of the class.